Nutritional quality of ready-to-eat breakfast cereals using the front-of-pack nutrition labelling system - Nutri-Score - Matias, Filipa (2020)
According to the most recent Portuguese National Food, Nutrition and Physical Activity Survey (2015-2016), it is estimated that 5.9 million Portuguese are overweight (more than 50% of the population), and this prevalence increases to 8 out of every 10 among the elderly. In the context of government strategies to tackle obesity and diet-related disease, a number of different nutrient profile models have been proposed and several applications have been identified. One of purposes of nutrient profiling systems is nutrition labelling to help consumers to make healthier food choices. A French front-of-pack labelling system named Nutri-Score classifies food into 1 of 5 classes, each associated with a colour and letter (from green/A to dark orange/E). The aim of this study was to assess the healthiness of ready-to-eat breakfast cereals (RTEBC), within 5 categories of nutritional quality, using Nutri-Score system. A nutritional database was constructed for 50 RTEBC that were collected from 3 food retail chains in the Lisbon area. RTEBC were classified as children’s cereals and non-children’s cereals. The nutritional data collected included: energy (kJ), saturated fat (g), total sugar (g) and sodium (mg). In our study, “Healthy” category corresponds to “dark green” and “light green” and “Less healthy” category corresponds to “yellow”, “light orange” and “dark orange”. The majority of breakfast cereals studied were categorized as “yellow” (60%; n=30) and that also apply to children’s (57.1%; n= 16) and non-children’s cereals (63.6%; n=14). Children’s cereals were distributed within 3 categories (light green, yellow and light orange) and only 17.9% (n=5) can be classified as “Healthy”. For non-children’s cereals, 18.1% (n=4) can be classified as “Healthy”. On the whole, only 18% (n=9) of RTEBC were considered as “Healthy”. Nutri-Score system seems to be an important tool in allowing consumers to better understand nutritional labelling and making healthier food choices.